POLA/CARA BELAJAR: PENERAPAN METODE PENEMUAN (DISCOVERY DAN INQUIRY) PADA KEGIATAN LABORATORIUM BIOKIMIA DI JURUSAN PENDIDIKAN BIOLOGI - Surtikanti, Hertien; Adisenjadja, Yusuf Hilmi; Fitriani, Any (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2001)
Practical exercise is a learning process in science that can not be separated from the whole learning process. Based on experience, students of Biology Education Department are not able to relate directly between theory and practical exercise in Biochemistry. In order to achieve this relevancy, the ‘discovery and inquiry’ method was implemented at Biology Education Department UPI. For comparison, convensional method (control) was implemented in other class. Each group has different practical exercise notes. This activity was done with three subjects in five meeting. The increasing products of two treatments was evaluated from two sources (a) reports that were submitted after the practical exercises and (b) quiz test for each subject. The submitted reports showed that the two classes (control and experiment) wrote an exact summary and make a table for an observation data. Score for three subjects (carbohydrate, lipid and amino acid) was significantly different between control and experiment. Experiment class had score higher than that in control class.